Implementing and adopting ebXML formatting of Business Transaction in Bangladesh - Rahman, Sanjid (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.